Dinâmica da ocupação e uso do solo em Londrina (PR): um olhar sobre a interface urbano-rural - Amarildo Souza de Paula; Omar Neto Fernandes Barros; Rigoberto Lázaro Prieto Cainzos; Ricardo Ralichi (Confins)
The core of this study is related to the recent changes in soil/land use and to the trends in physical/territorial expansion of Londrina-PR. Besides its diversified economical dynamism (industrial and agricultural capital) since its foundation, the city has been unable to control the speculative real estate business, the sole responsible for its physical-territorial development, creating a fragmented, socially segregated and environment degrading urban growth.  Findings from this study help recognize, within the limitations imposed by its scope, the need to define and implement public management policies and strategies for the rural land/soil use and occupation in the surrounding areas of Londrina.